Early biotic stress detection in tomato (Solanum lycopersicum) by BVOC emissions. (December 2017) - Kasal-Slavik, Tina; Eschweiler, Julia; Kleist, Einhard; Mumm, Roland; Goldbach, Heiner E.; Schouten, Alexander; Wildt, Jürgen
Abstract: We investigated impacts of early and mild biotic stress on Biogenic Volatile Organic Compounds (BVOC) emissions from tomato in order to test their potential for early (biotic) stress detection. Tomato plants were exposed to two common fungal pathogens, Botrytis cinerea and Oidium neolycopesici and the sap-sucking aphid Myzus persicae . Furthermore, plants were exposed to methyl jasmonate (MeJA) in order to identify BVOC emissions related to activation of jasmonic acid (JA) signalling pathway. These emissions where then used as a reference for identifying active JA signalling pathway in plants at early stages of biotic stress. After infection by the necrotrophic fungus B. cinerea, changes in BVOC emissions indicated that tomato plants had predominantly activated the jasmonic acid (JA) signalling pathway. The plants were able to modify their defence pathways in order to overcome fungal infection. When tomato plants were infected with the biotrophic fungus O. neolycopersici, only minor changes in BVOC emissions were observed with additional emissions of the sesquiterpene α-copaene. α-copaene emissions allowed the identification of general biotic stress in the plants, without pinpointing the actual triggered defence pathway. BVOC emissions during M. persicae attack had changed before the occurrence of visual symptoms. Despite low infestation rates, plants emitted methyl salicylate indicating activation of the SA-mediated defence pathway. Graphical abstract: Even early biotic stress alters biogenic volatile emissions that might be usable for early stress detection.